Modified diaphragm, preparation method and application thereof, and lithium-sulfur battery

By using a composite coating of a molecular sieve loaded with metal oxides and a conductive carbon material in the lithium-sulfur battery separator, combined with catalytic metal, the problem of shuttle effect of lithium-sulfur battery is solved, the battery capacity and cycling performance are improved, and the high capacity and cycling performance are met. Energy density battery requirements.

CN119231098AInactive Publication Date: 2024-12-31CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310772830.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The shuttle effect generated by lithium-sulfur batteries during electrochemical charging and discharge leads to a reduction in battery capacity and cycle performance. The physical barrier measures of the existing technology are limited in effect and cannot meet the needs of new energy electric vehicles and large-capacity energy storage systems for high-energy density batteries. demand.

Method used

Using a molecular sieve loaded with metal oxides as a separator, combining conductive carbon materials and binders to form a composite coating, using the pore structure of the molecular sieve and the chemical adsorption of the metal oxide to inhibit the migration and diffusion of polysulfides, and through the introduction of catalysis Metals improve the transfer performance of lithium ions and the conversion reaction kinetics of polysulfides.

Benefits of technology

The capacity and circulation performance of lithium-sulfur batteries are significantly improved, the suspension of shuttle effect is enhanced, and the rate performance and circulation stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004308410060000131
    Figure BDA0004308410060000131
Patent Text Reader

Abstract

The invention provides a modified diaphragm, a preparation method and application thereof and a lithium-sulfur battery, the modified diaphragm comprises a support membrane and a composite coating on the surface of the support membrane, the composite coating contains a molecular sieve loaded with a metal oxide, a conductive carbon material and a binder, and in the molecular sieve loaded with the metal oxide, the conductive carbon material and the binder are bonded together. The amount of the metal oxide is 0.1-15 wt% of the molecular sieve. When the modified diaphragm disclosed by the invention is applied to the lithium-sulfur battery diaphragm, on one hand, migration and diffusion of polysulfide in the battery can be physically prevented by utilizing the pore structure of the molecular sieve, on the other hand, the polysulfide can be chemically adsorbed through the metal oxide, and the shuttle effect problem of the lithium-sulfur battery can be more effectively relieved by combining the two. In addition, catalytic metal is further introduced into the molecular sieve, so that the conductivity of the positive electrode side of the diaphragm can be improved by using the metal, and the conversion reaction kinetics of polysulfide can be enhanced by using the catalytic property of the metal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery separators, and particularly to a modified separator and its preparation method and application, as well as a lithium-sulfur battery. Background Art

[0002] With the increasing energy demand, it is crucial to explore alternative energy storage systems with higher specific capacities to alleviate the over-reliance on lithium-ion batteries. Due to its high theoretical specific capacity (1675 mAh / g) and theoretical energy density (2600 Wh / kg), the lithium-sulfur battery is highly competitive in the next generation of high-energy rechargeable batteries. In addition, the active material sulfur of its positive electrode material also has the advantages of rich natural resources, low price, and environmental friendliness.

[0003] However, the commercial application of current lithium-sulfur batteries still faces many problems. The side reaction "shuttle effect" inside the battery is the biggest obstacle restricting its application. Specifically, the shuttle effect means that a series of sulfur-containing intermediate products are generated during the electrochemical charge and discharge process of lithium-sulfur batteries. Long-chain polysulfides (Li2S x , 2 < x ≤ 8) are soluble in the electrolyte, and then under the action of the concentration gradient and electric field, they penetrate through the conventional polyolefin separator and finally react chemically with the lithium negative electrode, resulting in the loss of active substances and an increase in battery internal resistance, thereby causing a decrease in battery capacity and cycling performance. In addition, the charge and discharge process of lithium-sulfur batteries involves multiple solid-liquid conversions, and the electronic conductivities of sulfur and the discharge end product lithium sulfide are poor. Therefore, the conversion reaction kinetics of polysulfides is slow, and the battery rate performance is poor.

[0004] Currently, the prior art has used molecular sieves to modify conventional separators to inhibit the shuttle effect of lithium-sulfur batteries, such as CN107546356A and CN103490027A. They utilize the physical barrier effect of molecular sieves to limit the migration and diffusion of Li2S x in the electrolyte to a certain extent, thereby improving battery performance.

[0005] In order to enable (lithium-sulfur) batteries to meet the requirements of new energy electric vehicles and large-capacity energy storage systems for higher energy density batteries, it is still necessary to develop battery separators with further improved performance. Summary of the Invention

[0006] The purpose of the present invention is to provide a modified separator that can improve the capacity and cycling performance of the battery.

[0007] The inventors of the present invention have discovered through extensive research that ordinary molecular sieves selectively prevent the migration and diffusion of polysulfides inside the battery through their pore structure. This single physical barrier effect is relatively limited, and the molecular sieves need to be further modified to enhance the inhibition of the shuttle effect, thereby further improving the capacity and cycle performance of the battery.

[0008] At the same time, further research found that by using molecular sieves loaded with metal oxides for lithium-sulfur battery separators, on the one hand, the pore structure of the molecular sieve can be used to physically prevent the migration and diffusion of polysulfides inside the battery, and on the other hand, polysulfides can be chemically adsorbed by metal oxides. The combination of the two can more effectively alleviate the shuttle effect problem of lithium-sulfur batteries.

[0009] At the same time, further research has found that the introduction of catalytic metals into the molecular sieve can not only improve the conductivity of the positive electrode side of the separator by using the metal, but also enhance the conversion reaction kinetics of polysulfides by using the catalytic properties of the metal. In the case where the molecular sieve further contains lithium, the introduced lithium can provide a large number of sites for the adsorption and transmission of lithium ions during the battery cycle, improving the lithium ion transmission performance of the separator.

[0010] Therefore, the first aspect of the present invention provides a modified diaphragm, which includes a support membrane and a composite coating on the surface of the support membrane, wherein the composite coating contains: a molecular sieve loaded with metal oxide, a conductive carbon material and a binder, wherein the amount of metal oxide in the molecular sieve loaded with metal oxide is 0.1-15 weight % of the molecular sieve.

[0011] The second aspect of the present invention provides a method for preparing the modified diaphragm, the method comprising:

[0012] (1) mixing a molecular sieve loaded with a metal oxide with a conductive carbon material to obtain a mixture;

[0013] (2) dispersing the mixture and a binder in a solvent to obtain a coating slurry;

[0014] (3) The coating slurry is coated on the surface of the support membrane, and then the solvent is removed to obtain a modified diaphragm.

[0015] The third aspect of the present invention provides an application of the modified diaphragm in a lithium-sulfur battery.

[0016] A fourth aspect of the present invention provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and a separator, wherein the separator contains the modified separator described in the present invention.

[0017] The present invention has the following advantages:

[0018] The modified diaphragm of the present invention contains a molecular sieve loaded with metal oxide in the composite coating. When applied to lithium-sulfur battery diaphragms, on the one hand, the pore structure of the molecular sieve can be used to physically prevent the migration and diffusion of polysulfides inside the battery, and on the other hand, polysulfides can be chemically adsorbed by metal oxides. The combination of the two can more effectively alleviate the shuttle effect problem of lithium-sulfur batteries. In addition, further introducing catalytic metals into the molecular sieve can not only use the metal to improve the conductivity of the positive electrode side of the diaphragm, but also use the catalytic properties of the metal to enhance the conversion reaction kinetics of polysulfides.

[0019] According to a preferred embodiment of the present invention, when the molecular sieve further contains a Group IA metal such as lithium, the introduced lithium can provide a large number of sites for the adsorption and transmission of lithium ions during the battery cycle, thereby improving the lithium ion transmission performance of the separator. Therefore, the modified separator of the present invention can improve the capacity and cycle performance of the battery. DETAILED DESCRIPTION

[0020] The endpoints and any values ​​of the range disclosed in this article are not limited to the precise range or value, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, between the endpoint values ​​of each range, between the endpoint values ​​of each range and a separate point value, and between separate point values, one or more new numerical ranges can be combined with each other, and these numerical ranges should be considered as specifically disclosed in this article. Except in the embodiments, in this article, all numerical values ​​of parameters should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value.

[0021] The present invention provides a modified diaphragm, which comprises a support membrane and a composite coating on the surface of the support membrane, wherein the composite coating contains: a molecular sieve loaded with metal oxide, a conductive carbon material and a binder, wherein the amount of the metal oxide in the molecular sieve loaded with metal oxide is 0.1-15% by weight of the molecular sieve. The modified diaphragm of the present invention can improve the capacity and cycle performance of a battery.

[0022] According to a preferred embodiment of the present invention, in the molecular sieve loaded with metal oxide, the amount of metal oxide is 5-10 wt % of the molecular sieve, for example, 5 wt %, 6 wt %, 7 wt %, 8 wt %, 9 wt %, 10 wt %.

[0023] In the present invention, as long as the purpose of the present invention can be achieved, there is no limitation on the thickness of the composite coating. According to a preferred embodiment of the present invention, the thickness of the composite coating is 2-35 μm, preferably 5-20 μm.

[0024] In the present invention, as long as the purpose of the present invention can be achieved, there is no restriction on the mass ratio of the conductive carbon material to the molecular sieve loaded with metal oxides in the composite coating. According to a preferred embodiment of the present invention, in the composite coating, the mass ratio of the conductive carbon material to the molecular sieve loaded with metal oxides is 0.1-1, preferably 0.12-0.35, for example, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30, 0.31, 0.32, 0.33, 0.34, 0.35.

[0025] In the present invention, as long as the purpose of the present invention can be achieved, there is no restriction on the mass ratio of the binder to the molecular sieve loaded with metal oxide in the composite coating. According to a preferred embodiment of the present invention, in the composite coating, the mass ratio of the binder to the molecular sieve loaded with metal oxide is 0.05-0.9, preferably 0.1-0.3, for example, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, 0.26, 0.27, 0.28, 0.29, 0.30.

[0026] According to a preferred embodiment of the present invention, the molecular sieve loaded with metal oxide preferably contains: a molecular sieve and a metal element and a metal oxide loaded on the molecular sieve, thereby further improving the capacity and cycle performance of the battery.

[0027] According to a preferred embodiment of the present invention, more preferably, the amount of the metal element is 0.5-5% by weight of the molecular sieve, preferably 1-3% by weight, such as 1%, 2%, and 3% by weight; the amount of the metal oxide is 1.5-8% by weight of the molecular sieve, such as 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, and 8% by weight. This can further improve the capacity and cycle performance of the battery.

[0028] In the present invention, the metal element of the metal oxide can be selected from a wide range. For the present invention, preferably, the metal element in the molecular sieve loaded with metal oxide contains one or more of Group VIII metal elements, Group VIIB metal elements, and Group IA metal elements. More preferably, the metal element is selected from one or more of Co, Fe, Ni, Mn and Li.

[0029] According to a preferred embodiment of the present invention, preferably, the metal element in the molecular sieve loaded with metal oxide contains a first metal element and a second metal element; the first metal element contains one or more of group VIII metal elements and group VIIB metal elements, and the second metal element contains group IA metal elements. This can further improve the capacity and cycle performance of the battery.

[0030] According to a preferred embodiment of the present invention, preferably, the first metal element exists in the form of a simple substance and an oxide at the same time, and the content of the first metal simple substance is 1-3 weight% of the molecular sieve, for example, 1 weight%, 2 weight%, 3 weight%; the content of the first metal oxide is 1.5-8 weight% of the molecular sieve, for example, 1.5 weight%, 2 weight%, 3 weight%, 4 weight%, 5 weight%, 6 weight%, 7 weight%, 8 weight%.

[0031] According to a preferred embodiment of the present invention, preferably, the first metal element is selected from one or more of Co, Fe, Ni and Mn, thereby further improving the capacity and cycle performance of the battery.

[0032] According to a preferred embodiment of the present invention, preferably, the second metal element is selected from Li, thereby further improving the capacity and cycle performance of the battery.

[0033] According to a preferred embodiment of the present invention, the amount of the second metal element is preferably 0.1-5% by weight, preferably 0.2-2% by weight, such as 0.2%, 1%, or 2% by weight of the molecular sieve, thereby further improving the capacity and cycle performance of the battery.

[0034] According to a preferred embodiment of the present invention, the types of the molecular sieve loaded with metal oxides can be selected from a wide range, and all common molecular sieves on the market can be used in the present invention. For the present invention, it is preferred that the molecular sieve loaded with metal oxides has a chemical composition shown as "xM2O·ySiO2·zAl2O3", wherein 0.01≤x / y≤0.2, 10≤y / z≤50, and M is one or two selected from Na and K; preferably, M is Na.

[0035] According to a preferred embodiment of the present invention, the molecular sieve loaded with metal oxide has at least one topological structure selected from MFI, MWW, GIS, BEC, FAU and MOR, preferably has a topological structure of MFI.

[0036] In the present invention, there is no special requirement for the support membrane, and commonly used support membranes can be used in the present invention. According to a preferred embodiment of the present invention, the material of the support membrane of the present invention includes but is not limited to at least one of polyethylene, polypropylene, polyimide, polyacrylonitrile, polyethylene terephthalate, polytetrafluoroethylene and polyvinylidene fluoride; preferably polyethylene and / or polypropylene.

[0037] In the present invention, there is no special requirement for the conductive carbon material, and commonly used conductive carbon materials can be used in the present invention. According to a preferred embodiment of the present invention, the conductive carbon material includes but is not limited to at least one of graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, carbon nanofibers, acetylene black, Super P and Ketjen black; preferably at least one of graphene, graphene oxide and reduced graphene oxide.

[0038] In the present invention, there is no special requirement for the binder, and commonly used binders can be used in the present invention. According to a preferred embodiment of the present invention, the binder includes but is not limited to at least one of polyvinyl alcohol, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl pyrrolidone, styrene-butadiene rubber and polyacrylate; preferably polyvinylidene fluoride.

[0039] The present invention has no special requirements for the preparation method of the modified diaphragm. As long as the modified diaphragm characteristics required by the present invention are met, the purpose of the present invention can be achieved. According to a preferred embodiment of the present invention, the present invention provides a preparation method of the modified diaphragm, which comprises:

[0040] (1) mixing a molecular sieve loaded with a metal oxide with a conductive carbon material to obtain a mixture;

[0041] (2) dispersing the mixture and a binder in a solvent to obtain a coating slurry;

[0042] (3) The coating slurry is coated on the surface of the support membrane, and then the solvent is removed to obtain a modified diaphragm.

[0043] According to a preferred embodiment of the present invention, the optional range of the types of the solvent is relatively wide. According to a preferred embodiment of the present invention, the solvent includes but is not limited to at least one of deionized water, anhydrous ethanol, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone, preferably N-methylpyrrolidone.

[0044] In the present invention, the coating method in step (3) can be a conventional method in the art. According to a preferred embodiment of the present invention, the coating in step (3) is at least one of a casting method, a blade coating method, a spray coating method, and a spin coating method, preferably a blade coating method. By adopting the above-mentioned preferred method, the rate performance and cycle stability of the battery can be further improved.

[0045] In the present invention, there is no special requirement for the preparation method of the molecular sieve loaded with metal oxides. For the present invention, the preparation method of the molecular sieve loaded with metal oxides preferably comprises: mixing a metal salt solution with the molecular sieve, and then drying and calcining. Preferably, partial reduction of the metal oxide is performed after calcining. By adopting the above-mentioned preferred method, the rate performance and cycle stability of the battery can be further improved.

[0046] In the present invention, when the metal is cobalt, iron, nickel or manganese, the metal salt solution is selected from at least one of a cobalt salt solution, an iron salt solution, a nickel salt solution and a manganese salt solution.

[0047] In the present invention, when the second metal is lithium, the lithium ion solution is selected from at least one of a lithium chloride solution, a lithium acetate solution, a lithium sulfate solution, and a lithium nitrate solution.

[0048] In the present invention, more preferably, the method for preparing the molecular sieve loaded with metal oxide comprises:

[0049] The first metal salt solution is mixed with the molecular sieve, and then dried and calcined. Preferably, after calcination, the first metal oxide is partially reduced to obtain a molecular sieve loaded with the first metal oxide, and the molecular sieve loaded with the first metal oxide is mixed with the second metal salt solution, exchanged, washed, and dried. By adopting the above-mentioned preferred embodiment, the rate performance and cycle stability of the battery can be further improved.

[0050] In the present invention, there is no special requirement for the calcination conditions. According to a preferred embodiment of the present invention, preferably, the calcination conditions include: the atmosphere is air.

[0051] In the present invention, there is no special requirement for the calcination conditions. According to a preferred embodiment of the present invention, preferably, the calcination conditions include: a temperature of 300-800°C.

[0052] In the present invention, preferably, according to a preferred embodiment of the present invention, the calcination conditions include: the calcination time is 1-4h.

[0053] In the present invention, as long as the purpose of the present invention can be achieved, the reduction conditions can be conventionally selected in the art. According to a preferred embodiment of the present invention, the reduction conditions include: the atmosphere is hydrogen.

[0054] In the present invention, as long as the purpose of the present invention can be achieved, the reduction conditions can be conventionally selected in the art. According to a preferred embodiment of the present invention, the reduction conditions include: a temperature of 600-800°C.

[0055] In the present invention, as long as the purpose of the present invention can be achieved, the reduction conditions can be conventionally selected in the art. According to a preferred embodiment of the present invention, the reduction conditions include: the reduction time is 10-30 minutes.

[0056] In the present invention, the exchange is carried out under the following conditions: temperature of 40-100° C., liquid-to-solid ratio of 10-50; preferably, the exchange is carried out 1-3 times.

[0057] The present invention provides application of the modified diaphragm of the present invention in a battery.

[0058] The present invention provides a lithium-sulfur battery, comprising a positive electrode, a negative electrode and a separator, wherein the separator contains the modified separator of the present invention.

[0059] The present invention will be described in detail below through examples.

[0060] Test method:

[0061] Assembly of lithium-sulfur battery samples:

[0062] First, prepare the positive electrode: sublimated sulfur, conductive agent Ketjen black, and binder polyvinylidene fluoride are mixed in a mass ratio of 6:3:1, and N-methylpyrrolidone is added to form a positive electrode slurry; the positive electrode slurry is coated on aluminum foil and dried to obtain a positive electrode. Then, 2025 button cells are assembled in an argon glove box with a water and oxygen content of less than 0.1ppm: the positive electrode shell, positive electrode, diaphragm, lithium negative electrode, foam nickel, and negative electrode shell are assembled in sequence, and 100μL of electrolyte is added. The electrolyte used is a mixed solution of 1,3-dioxolane / ethylene glycol dimethyl ether (DOL / DME, volume ratio of 1:1) containing 1mol / L lithium bis(trifluoromethylsulfonyl)imide and 0.2mol / L lithium nitrate.

[0063] The rate performance and cycle performance of the lithium-sulfur battery samples prepared as described above were tested by constant current charge and discharge tests.

[0064] Rate performance test:

[0065] The lithium-sulfur battery sample was charged and discharged for 5 cycles at 1C (1C = 1675 mA / g) in the voltage range of 1.7-2.7 V. The charge specific capacity of the corresponding charge and discharge cycle was recorded, and the average charge specific capacity of the 5 cycles was calculated:

[0066] Average charge capacity of 5 cycles at 1C = (sum of charge capacities from 1st to 5th cycle) / 5

[0067] Similarly, the charge-discharge cycle was repeated for 5 cycles at 2C and 3C, and the average charge specific capacity of the 5 cycles at 2C and 3C was measured.

[0068] Cycle performance test:

[0069] The lithium-sulfur battery sample was charged and discharged for 2 cycles at 0.1 and 0.2C in the voltage range of 1.7-2.7V, and then the lithium-sulfur battery sample was cycled for 100 cycles at 0.5C. The charge specific capacity after the first cycle at 0.5C and the 100th cycle was recorded. The capacity retention rate after 100 cycles at 0.5C was calculated according to the following formula to characterize the cycle performance.

[0070] Capacity retention rate after 100 cycles = charge specific capacity at 100th cycle / charge specific capacity at 1st cycle * 100%.

[0071] Example 1

[0072] Preparation of modified diaphragm:

[0073] (1) 5 g of a raw molecular sieve (MFI molecular sieve having a composition of Na2O·20SiO2·Al2O3) was immersed in a cobalt acetate solution having a concentration of 0.2 mol / L, dried at 80°C in air, and then further treated at 700°C in air for 2 h to obtain an MFI molecular sieve loaded with cobalt oxide (the amount of metal oxide was 7.5% by weight of the molecular sieve);

[0074] (2) grinding and mixing 0.35 g of the MFI molecular sieve loaded with cobalt oxide and 0.1 g of graphene in a mortar to obtain a mixture;

[0075] (3) dispersing the mixture and 0.05 g of polyvinylidene fluoride in N-methylpyrrolidone, stirring and mixing evenly to obtain a coating slurry;

[0076] (4) The coating slurry is evenly coated on one side of the polyethylene / polypropylene base film by a doctor blade method, and then dried to remove the solvent, thereby obtaining a modified diaphragm having a composite coating evenly distributed on one side of the polymer base film, wherein the thickness of the composite coating is 15 μm.

[0077] Performance test of modified diaphragm:

[0078] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0079] Example 2

[0080] Example 1 was repeated, except that the cobalt acetate solution in step (1) was replaced with ferric acetate solution to obtain an MFI molecular sieve loaded with iron oxide (the amount of metal oxide was 6.3 wt % of the molecular sieve); the molecular sieve in step (2) was adjusted to 0.4 g, and the graphene was adjusted to 0.05 g; and the thickness of the composite coating in step (4) was adjusted to 5 μm.

[0081] Performance test of modified diaphragm:

[0082] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0083] Example 3

[0084] Example 1 was repeated, except that the cobalt acetate solution in step (1) was replaced with nickel acetate solution to obtain an MFI molecular sieve loaded with nickel oxide (the amount of metal oxide was 5 wt % of the molecular sieve); the molecular sieve in step (2) was adjusted to 0.45 g, and the graphene was adjusted to 0.15 g; and the thickness of the composite coating in step (4) was adjusted to 20 μm.

[0085] Performance test of modified diaphragm:

[0086] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0087] Example 4

[0088] Example 1 was repeated, except that the MFI molecular sieve loaded with cobalt oxide obtained in step (1) was subjected to lithium ion exchange, and the preparation method thereof was as follows:

[0089] 2 g of MFI molecular sieve loaded with cobalt oxide was subjected to lithium ion exchange with 0.5 mol / L LiCl solution (liquid-to-solid ratio of 20) at 80°C for 2 hours, followed by centrifugal washing. The lithium ion exchange was repeated twice and the obtained sample was dried at 100°C to obtain a lithium-containing MFI molecular sieve loaded with cobalt oxide (the lithium content was 1% by weight of the molecular sieve).

[0090] Performance test of modified diaphragm:

[0091] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0092] Example 5

[0093] Example 1 was repeated, except that the MFI type molecular sieve loaded with cobalt oxide obtained in step (1) was partially reduced, and the preparation method thereof was as follows:

[0094] 2 g of MFI molecular sieve loaded with cobalt oxide was treated at 700° C. in a hydrogen atmosphere for 15 min to obtain an MFI molecular sieve loaded with metallic cobalt and cobalt oxide (elemental cobalt: 1.9 wt %, cobalt oxide 5 wt %).

[0095] Performance test of modified diaphragm:

[0096] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0097] Example 6

[0098] Example 1 was repeated, except that the MFI molecular sieve loaded with cobalt oxide obtained in step (1) was partially reduced and lithium ion exchanged, and the preparation method was as follows:

[0099] (1) 2 g of MFI molecular sieve loaded with cobalt oxide was treated at 700° C. in a hydrogen atmosphere for 15 min to obtain an MFI molecular sieve loaded with metallic cobalt and cobalt oxide.

[0100] (2) 2 g of MFI molecular sieve loaded with metallic cobalt and cobalt oxide was subjected to lithium ion exchange with 0.5 mol / L LiCl solution (liquid-to-solid ratio of 20) at 80°C for 2 hours, followed by centrifugal washing. The lithium ion exchange was repeated twice and the obtained sample was dried at 100°C to obtain a lithium-containing MFI molecular sieve loaded with metallic cobalt and cobalt oxide (elemental cobalt: 1.9 wt%, cobalt oxide 5 wt%, lithium element: 1 wt%).

[0101] Performance test of modified diaphragm:

[0102] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0103] Example 7

[0104] Example 1 was repeated, except that the amount of graphene in step (2) was adjusted to 0.4 g.

[0105] Performance test of modified diaphragm:

[0106] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0107] Example 8

[0108] Example 1 was repeated, except that the graphene in step (2) was replaced by Super P; and the N-methylpyrrolidone in step (3) was replaced by dimethyl sulfoxide.

[0109] Performance test of modified diaphragm:

[0110] According to the description of the test method above, the prepared modified separator was used to assemble lithium-sulfur battery samples and perform performance tests. The specific test results are shown in Table 1.

[0111] Comparative Example 1

[0112] Example 1 was repeated, except that the MFI molecular sieve loaded with cobalt tetroxide was replaced with a common MFI molecular sieve.

[0113] Example 1 was repeated to assemble a lithium-sulfur battery sample using the prepared modified diaphragm and perform a performance test. The test results are shown in Table 1.

[0114] Table 1 Performance test results of lithium-sulfur battery samples

[0115]

[0116] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

[0117] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A modified diaphragm, characterized in that: The modified diaphragm comprises a support membrane and a composite coating on the surface of the support membrane, wherein the composite coating contains: a molecular sieve loaded with metal oxides, a conductive carbon material and a binder, wherein the amount of the metal oxide in the molecular sieve loaded with metal oxides is 0.1-15% by weight of the molecular sieve.

2. The modified diaphragm according to claim 1, wherein In the molecular sieve loaded with metal oxide, the amount of metal oxide is 5-10 wt % of the molecular sieve; and / or The thickness of the composite coating is 2-35 μm, preferably 5-20 μm; and / or In the composite coating, the mass ratio of the conductive carbon material to the molecular sieve loaded with metal oxide is 0.1-1, preferably 0.12-0.35; and / or In the composite coating, the mass ratio of the binder to the molecular sieve loaded with metal oxide is 0.05-0.9, preferably 0.1-0.

3.

3. The modified diaphragm according to claim 1 or 2, wherein: The molecular sieve loaded with metal oxides comprises: a molecular sieve and a metal element and a metal oxide loaded on the molecular sieve; More preferably, the amount of the metal element is 0.5-5% by weight, preferably 1-3% by weight, of the molecular sieve; and the amount of the metal oxide is 1.5-8% by weight of the molecular sieve.

4. The modified diaphragm according to any one of claims 1 to 3, wherein: The metal element in the molecular sieve loaded with metal oxide contains one or more of Group VIII metal elements, Group VIIB metal elements, and Group IA metal elements; preferably, the metal element is selected from one or more of Co, Fe, Ni, Mn, and Li; Preferably, the metal element in the molecular sieve loaded with metal oxide contains a first metal element and a second metal element; the first metal element contains one or more of Group VIII metal elements and Group VIIB metal elements, and the second metal element contains Group IA metal elements; More preferably, The first metal element exists in the form of a single substance and an oxide at the same time, and the content of the first metal single substance is 1-3% by weight of the molecular sieve; the content of the first metal oxide is 1.5-8% by weight of the molecular sieve; The first metal element is selected from one or more of Co, Fe, Ni and Mn; and / or The second metal element is selected from Li; and / or The amount of the second metal element is 0.1-5% by weight, preferably 0.2-2% by weight, of the molecular sieve.

5. The modified diaphragm according to any one of claims 1 to 4, wherein: The molecular sieve loaded with metal oxide has a chemical composition represented by "xM2O·ySiO2·zAl2O3", wherein 0.01≤x / y≤0.2, 10≤y / z≤50, M is one or two selected from Na and K; preferably, M is Na; and / or The molecular sieve loaded with metal oxide has at least one topological structure selected from MFI, MWW, GIS, BEC, FAU and MOR, preferably has a topological structure of MFI.

6. The modified diaphragm according to any one of claims 1 to 5, wherein: The material of the support film is at least one of polyethylene, polypropylene, polyimide, polyacrylonitrile, polyethylene terephthalate, polytetrafluoroethylene and polyvinylidene fluoride; preferably polyethylene and / or polypropylene; and / or The conductive carbon material is at least one of graphene, graphene oxide, reduced graphene oxide, carbon nanotubes, carbon nanofibers, acetylene black, Super P and Ketjen black; preferably at least one of graphene, graphene oxide and reduced graphene oxide; and / or The binder is at least one of polyvinyl alcohol, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl pyrrolidone, styrene-butadiene rubber and polyacrylate, and preferably polyvinylidene fluoride.

7. The method for preparing the modified diaphragm according to any one of claims 1 to 6, characterized in that: The method includes: (1) mixing a molecular sieve loaded with a metal oxide with a conductive carbon material to obtain a mixture; (2) dispersing the mixture and a binder in a solvent to obtain a coating slurry; (3) coating the coating slurry on the surface of the support membrane, and then removing the solvent to obtain a modified diaphragm; Preferably, The solvent in step (2) is selected from at least one of deionized water, anhydrous ethanol, N,N-dimethylacetamide, N,N-dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone, preferably N-methylpyrrolidone; and / or The coating in step (3) is at least one of casting, blade coating, spray coating and spin coating, preferably blade coating.

8. The preparation method according to claim 7, wherein: The preparation method of the molecular sieve loaded with metal oxide comprises: Mixing the metal salt solution with the molecular sieve, and then drying and calcining. Preferably, after calcining, partially reducing the metal oxide; More preferably, the method for preparing the molecular sieve loaded with metal oxide comprises: The first metal salt solution is mixed with the molecular sieve, and then dried and calcined. Preferably, after calcination, the first metal oxide is partially reduced to obtain a molecular sieve loaded with the first metal oxide, and the molecular sieve loaded with the first metal oxide is mixed with the second metal salt solution, exchanged, washed and dried; Preferably, The calcination conditions include: an air atmosphere, a temperature of 300-800° C., and a time of 1-4 hours; and / or The reduction conditions include: hydrogen atmosphere, temperature of 600-800° C., and reduction time of 10-30 minutes; and / or The exchange is carried out under the following conditions: temperature of 40-100° C., liquid-to-solid ratio of 10-50; preferably, the exchange is carried out 1-3 times.

9. Use of the modified diaphragm according to any one of claims 1 to 6 in a battery.

10. A lithium-sulfur battery, characterized in that: The invention comprises a positive electrode, a negative electrode and a separator, wherein the separator comprises the modified separator according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Metal element modified ZSM-5 molecular sieve composite membrane as well as preparation method and application thereof

    CN102350229A

  • Lithium ion battery and anode thereof

    CN102709521A

  • Lithium-sulfur battery anode material comprising porous metal and preparation method thereof

    CN102723470A

  • Functionalized porous material as well as preparation method and application thereof

    CN107230788A

  • MOF-modified cellulosic material intermediate layer for lithium-sulfur battery and preparation method

    CN112391700A